PELAKSANAAN KEWAJIBAN ORANG TUA TERHADAP ANAK DISABILITAS DI SEKOLAH LUAR BIASA NEGERI PEMBINA PEKANBARU DALAM PERSPEKTIF HUKUM PERDATA - Khairani, Khairani; Firdaus, Firdaus; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Marriage creates a legal relationship between parents and children. In Article 45 of Law Number 1 of 1974 concerning Marriage states (1) Both parents are obliged to maintain and educate their children as well as possible (2) Parental obligations referred to in paragraph (1) of this article are valid until the child marries or can stand alone obligations continue even though the marriage between the two parents breaks up.The problem that the author makes in this study is the implementation of the obligation of parents to children with disabilities in Sekolah Luar Biasa Negeri Pembina Pekanbaru. Research methods are juridical empirical or sociological legal research. The data sources used in this study are derived from primary data and secondary data. Data analysis using qualitative data analysis.The results of this study about the implementation of the obligations of parents to children with disabilities in Sekolah Luar Biasa Negeri Pembina Pekanbaru in the perspective of civil law that regulates the obligations of parents still found deficiencies in its implementation. There are still parents who do not know the development of their children and the presence of disability children who are missing. The conclusion if referring to Article 45 paragraph 1 of Law Number 1 Year 1974 concerning Marriage that parents have not been good at taking care of their children.Keywords: Children, Disability, Obligations, Parents. Alimentation.